138k views
19 votes
Please help. don’t understand :((

Please help. don’t understand :((-example-1
User Tilak
by
6.3k points

2 Answers

10 votes

Answer:

f(19) = -
(27)/(7)

Explanation:

Given

f(x) =
(3)/(x+2) -
√(x-3)

To evaluate f(19), substitute x = 19 into f(x) , that is

f(19) =
(3)/(19+2) -
√(19-3)

=
(3)/(21) -
√(16)

=
(1)/(7) - 4

=
(1)/(7) -
(28)/(7)

= -
(27)/(7)

User Spacehunt
by
6.0k points
14 votes

Answer:

Explanation:

place x = 19

f(19) = 3 / 19 + 2 - Sqrt 21 - 3

= 3/21 - 4

= - 81/21

= - 27/7

User Mark Piller
by
6.2k points